Agricultural crisis and rural organisation in the Cape : 1929-1933 - Hofmeyr, William Andrew (Department of Historical Studies, 2016)
This thesis explores the relationship between rural struggles and popular organisation in the Cape between 1928 and 1933. It focuses on the attempts by militants in the ANC(Western Province) and later the Independent ANC to organise in the rural areas during a period of crisis for agriculture. In the first chapter the history and trends in the nationalist movement before 1930 is discussed. It is argued that the conservative petty bourgeoisie dominated the organisation for much of the time, but that more militant positions were adopted on a few rare occasions. The second chapter endeavours to show that the transition to capitalist agriculture had been completed in the Western Cape. ·It then examines the specificity of the crisis in agriculture during the Depression: a crisis which was manifested in the form of an acute labour shortage on the farms, combined with unemployment in the towns. This, it is argued, provided a fertile ground for organisation The third chapter examines the rural struggles in the Western Cape. It analyses the alliance in the ANC(WP) between the moderate Garveyists and the militants linked to the Communist Party, and the reasons for the subsequent breakdown of this alliance. It discusses both the success of the organisation in coping with violent repression, and its failure to cope with the state's more subtle strategies. The militants were eventually expelled from the ANC. Most rural branches then broke away to form the Independent ANC. Chapter 4 discusses the formation of the IANC and raises some questions about the nature of its political programme. It then proceeds to focus on organisation in the Southern Cape where all the branches had joined the IANC. The fifth chapter discusses the organisation in the Midlands area of the Eastern Cape. It attempts to explain the lack of success in Graaff-Reinett. It then proceeds to examine the organisation in Middelburg where is appears that it had learnt to cope with at least some of the problems experienced in the Western Cape. The sixth chapter analyses in some detail the issues that were taken up by the IANC in the Midlands, and how these were reflected in its discourse. Among the issues raised are unemployment, resistance to passes and local control measures, the problem of women's participation and the struggle that was waged against the conservative petty bourgeoisie in the ANC. The seventh chapter first discusses organisation in Cradock. It then proceeds to describe how the struggle in the Midlands built up to a climax at the end of 1931, until massive repression smashed the organisation. Thereafter the organisation continued only at a low level. The conclusion attempts to draw together some of the themes raised above. First, it discusses the relationship between the petty bourgeoisie and the militants. Second, it argues that the organisation's approach was essentially "agitational", and that this accounts partly for its effectiveness, as well as many of its weaknesses. Lastly an attempt is made to evaluate the significance of the organisation.